Improving the Effectiveness of the Solid-Solution-Strengthening Elements Mo, Re, Ru and W in Single-Crystalline Nickel-Based Superalloys - Tobias Gaag (MDPI AG, 2021)
Tailoring the partitioning behavior of solid solution strengtheners is a crucial design strategy for advanced Ni-based superalloys. The goal of this study was to maximize the enrichment of Mo, Re, Ru and W in the γ-matrix phase. To determine the composition dependency of the partitioning behavior, a set of polycrystalline superalloys with varying contents of these solid solution-strengthening elements and a W-containing single-crystalline alloy series with varying concentrations of the γ′-forming elements Ta and Ti was produced. Assessed properties include phase compositions by electron-probe micro-analysis, phase transformation temperatures by differential scanning calorimetry and creep behavior. Re exhibits the most pronounced enrichment in the γ-matrix, followed by Mo, Ru and W. Due to the preference of the Al-sites in the γ′-phase in the order Ta > Ti > W > Mo > Re, the solid solution strengthening elements Mo, Re and W are displaced from the γ′-phase by increasing Ti and Ta contents. The investigated solutes do not directly influence the partitioning behavior of Ru as it prefers Ni-sites in the γ′-phase. Compressive creep experiments reveal a correlation between the content of solid solution strengtheners in the γ-phase and creep performance.